Representation of traumatic pages of national history: images of Alash Orda figures in the visual culture of modern KazakhstanN (Journal of history, 2023)
The article explores the forms of representation of tragic events in the history of Kazakhstan associated with the activities of the Alash Orda party in the contemporary visual culture of our country. The research of the images of the Alash party members is based on the methodology of memory studies and trauma studies. The aim of the article is to study the problems of actualisation and embodiment of the cultural memory of the traumatic past. Based on the monuments of contemporary painting, sculpture, design and conceptual art the author analyzes the modern representations of historical trauma, through which the meaning and potential of the past for the development of New Kazakhstan is revealed. The main attention is given to the works in which not only the names of historical figures who were victims of terror are named and included into the social field, but there is an attempt to "work through" this trauma, the task is not only to remember and commemorate, but also to deeply reflect the memory of the past, to reveal in it the brightest moments and problems.Keywords: Alash Orda, representation, cultural memory, sites of memory, acting out trauma, "working through" trauma, painting, sculpture, design, contemporary art.